The Peloponnesian War : a military study - Lazenby, J. F. (John Francis) (Warfare and history., 2004)
The range and extent of the Peloponnesian War of the fifth century BC has led to it being described as a ''world war'' in miniature. With the struggle between Athens and Sparta at its core, the twenty-seven-year conflict drew in states from all points of the compass; from Byzantion in the north, Crete in the south, Asia Minor in the east and Sicily in the west.